PERBEDAAN INTENSI MENDAPATKAN VAKSIN HUMAN PAPILLOMAVIRUS UNTUK MENCEGAH KANKER SERVIKS DI ANTARA WANITA DENGAN BERBAGAI TIPE PENGAMBIL KEPUTUSAN - Samaria, Dora; Simanungkalit, Sintha Fransiske (Nursing Current: Jurnal Keperawatan, 2025)
Despite the availability of cervical cancer prevention programs through Human Papillomavirus (HPV) vaccination in Indonesia, the overall immunization coverage remains limited. One of the main contributing factors is the low intention among the community to receive the HPV vaccine. Low intention may lead to limited vaccination uptake. This study aims to compare differences in intention to get HPV vaccination among three groups of female decision makers, namely, adult women who take their own vaccine decisions, adolescent girls who rely on their parents to decide on vaccination, and parents who help make decisions regarding HPV vaccination for their daughters. This study employed a quantitative approach with a cross-sectional design. Each group of decision makers consisted of 147 people, with a total of 441 respondents. The data collected were analyzed using Kruskal-Wallis test. The statistical analysis confirmed significant differences in intention among the three groups (p<0.001). The highest mean intention rank was in the adult women group (mean-rank=273.55), followed by parents (mean-rank=214.37), and the lowest in adolescent girls (mean-rank=175.09). Women's intention to receive the HPV vaccine is influenced by their level of independence in decision-making. Adult women with full decision-making autonomy demonstrated the highest intention. These findings highlight the need for tailored approaches in promoting HPV vaccination based on decision-making roles to improve vaccination uptake.